STUDY OF ADDITIVE, SIZE FRACTION AND COAL CONCENTRATION FOR COAL WATER FUEL - FAHMI SULISTYOHADI; GANDHI K. HUDAYA (Puslitbang tekMIRA, 2010)
Coal Water Fuel (CWF) is one of energy diversifications. It enables the coal to substitute fuel oil by existing installations because CWF could flow similar to the flow of liquid. Selections of additive, coal size fraction, ratio coal and water of CWF were studied in laboratory scale. Arutmin coal, processed with Upgraded Brown Coal (UBC) technology, was grouped to -60 and -200 meshes and then are mixed with water and small quantities of additive. Size fraction, coal concentration and additive type were varied to investigate their effects on CWF behavior. Results from concentration and penetration tests show that the best additive for CWF with size fraction - 200 mesh is DBS (Doacely Benzene Sulfanat) with optimum coal concentration is 51% using size - 60 mesh indicate, that the most stable CWF was resulted from CWF using DBS with optimum coal concentration 55 %. Results of using different size fraction that show the decrease of concentration and penetration rate from CWF with size fraction - 200 mesh is relatively constant compared to the CWF with size fraction – 60 mesh.